Morroniside Inhibits H2O2-Induced Podocyte Apoptosis by Down-Regulating NOX4 Expression Controlled by Autophagy In Vitro - Gao, Xue; Liu, Yi; Wang, Lin; Sai, Na; Liu, Yixiu; Ni, Jian (Frontiers in Pharmacology, 2020)
Podocyte apoptosis is the common pathological basis for the progression of various kidney diseases. The overexpression of NOX4, a key enzyme involved in oxidative stress, has been proved to participate in the occurrence of podocyte apoptosis. Autophagy is a kind of adaptive response of cells under stress. However, as a "double-edged sword", the effect of autophagy on apoptosis in different cells and conditions is complex and variable, which has not been fully explained yet. Morroniside, extracted from the traditional medicinal plant Cornus officinalis, has remarkable antioxidant and anti-apoptosis effects, and has been proven to inhibit the overexpression of NOX4 in kidney tissue. Therefore, H2O2 was used in this study to explore the effects of autophagy on podocyte NOX4 overexpression and apoptosis induced by oxidative stress, as well as the protection mechanism of morroniside in podocytes. The results showed that the autophagy activator rapamycin, as well as the autophagy inhibitor chloroquine, could induce podocyte apoptosis cultured in normal condition, and chloroquine could also significantly increased the NOX4 expression. The NOX4 expression and apoptosis rate of podocytes increased after H2O2 treatment, the expression of LC3-Ⅱ decreased, and the expressions of p62, mTOR, and p-mTOR increased. The intervention of morroniside and rapamycin improved autophagy activity and inhibited NOX4 overexpression and apoptosis induced by H2O2. And chloroquine reversed the inhibitory effect of morroniside on NOX4 overexpression and podocyte apoptosis. Taken together, our results suggest that the expression level of NOX4 in podocytes is regulated by autophagy activity. Morroniside can reduce oxidative stress induced podocyte apoptosis by restoring the damaged autophagy flux, and inhibit the overexpression of NOX4.